Growth and reproductive biology of the amphidromous shrimp Palaemon pandaliformis (Decapoda: Caridea) in a Neotropical river from northeastern Brazil - Paschoal, Lucas R. P. [UNESP] (2016)
Population biology, growth and reproductive aspects of the amphidromous shrimp Palaemon pandaliformis (Stimpson, 1871) were investigated in a Neotropical river of northeastern Brazil. The specimens were collected every month from September 2009 to August 2010. Total and monthly sex ratios deviated in favour of males. Von Bertalanffy growth parameters indicated that the females grew more rapidly, reached larger sizes, and had a longer life span than males. We also observed continuous reproductive activity and juvenile recruitment throughout the year. Relations between the number of eggs (fecundity) and body size indicated that fecundity in females increase with size. Compared with previous results, some population biology parameters of the freshwater population of P. pandaliformis differ from estuarine populations. The reproductive aspects analyzed here and their comparison with other marine species were consistent with the hypothesis that Palaemonidae species are undergoing an adaptation process and colonizing fresh water environments.